Transcranial focused ultrasound precise neuromodulation: a review of focal size regulation, treatment efficiency and mechanisms - Jin, Jie; Pei, Guangying; Ji, Zhenxiang; Liu, Xinze; Yan, Tianyi; Li, Wei; Suo, Dingjie (Frontiers in Neuroscience, 2024)
Ultrasound is a mechanical wave that can non-invasively penetrate the skull to deep brain regions to activate neurons. Transcranial focused ultrasound neuromodulation is a promising approach, with the advantages of noninvasiveness, high-resolution, and deep penetration, which developed rapidly over the past years. However, conventional transcranial ultrasound’s spatial resolution is low-precision which hinders its use in precision neuromodulation. Here we focus on methods that could increase the spatial resolution, gain modulation efficiency at the focal spot, and potential mechanisms of ultrasound neuromodulation. In this paper, we summarize strategies to enhance the precision of ultrasound stimulation, which could potentially improve the ultrasound neuromodulation technic.